All time is not one: memories, women and Capoeira (TEL Tempo, Espaço e Linguagem, 2024)
In this article, I seek to trace relationships between oral history, gender and Capoeira, considering the erasures and silencing of female voices in our history and in the historiography of Capoeira. I bring a discussion about historical records, feminisms and memory, including the racial issue, to address the recent discussion of women capoeiristas and the resistance and struggles of female Capoeira masters.